Wybrane aspekty związku kontroli zewnętrznej z controllingiem bankowym - Niewiadoma, Maria (Different Aspects the Connects the External Control With the Banking Controlling, 2005)
Elements of the banking system of control and the system of control in the bank. 13 principles of estimation systems of internal controls in banks (and banking controlling) are elaborated by the Basel Committee on Banking Supervision in Bazylea in 1998. Banking controlling and external control has been helpful in management in every financial system, especially during globalization process when every bank try to improve the activity, to reduce their exposures to certain sectors due to higher levels of capital usage.(original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1085, s. 305-315